Faktor-Faktor yang Mempengaruhi Kepuasan Konsumen Pengguna Layanan Pembelian Secara Daring: Peran Kepuasan Konsumen Sebagai Mediator - Nova Christian Mamuaya; Aditya Pandowo (Esensi: Jurnal Bisnis dan Manajemen, 2019)
The purpose of this study is to analyze the influence of several antecedents of customer satisfaction in the online shopping industry, namely site design, time savings, product variation, and shipping performance, and its consequence on customer satisfaction and word of mouth. This study uses purposive sampling with repeat buyer criteria. 100 samples qualify and deserve to be tested after testing their validity and reliability. The results showed that site design, time savings, and delivery performance significantly affected customer satisfaction. Meanwhile, site design, time savings, and product variations affect word of mouth. In addition, the results also confirm the hidden role of customer satisfaction as a partial mediating variable. Thus, the market must increase the availability of products and services to increase customer satisfaction in order to increase word of mouth activities.